Physiological and modeling evidence for focal transcranial electrical brain stimulation in humans: A basis for high-definition tDCS - Edwards, Dylan; Cortes, Mar; Datta, Abhishek; Minhas, Preet; Wassermann, Eric M.; Bikson, Marom (NeuroImage (Orlando, Fla.), 2013)
Transcranial Direct Current Stimulation (tDCS) is a non-invasive, low-cost, well-tolerated technique producing lasting modulation of cortical excitability. Behavioral and therapeutic outcomes of tDCS are linked to the targeted brain regions, but there is little evidence that current reaches the brain as intended. We aimed to: (1) validate a computational model for estimating cortical electric fields in human transcranial stimulation, and (2) assess the magnitude and spread of cortical electric field with a novel High-Definition tDCS (HD-tDCS) scalp montage using a 4×1-Ring electrode configuration. In three healthy adults, Transcranial Electrical Stimulation (TES) over primary motor cortex (M1) was delivered using the 4×1 montage (4× cathode, surrounding a single central anode; montage radius ~3cm) with sufficient intensity to elicit a discrete muscle twitch in the hand. The estimated current distribution in M1 was calculated using the individualized MRI-based model, and compared with the observed motor response across subjects. The response magnitude was quantified with stimulation over motor cortex as well as anterior and posterior to motor cortex. In each case the model data were consistent with the motor response across subjects. The estimated cortical electric fields with the 4×1 montage were compared (area, magnitude, direction) for TES and tDCS in each subject. We provide direct evidence in humans that TES with a 4×1-Ring configuration can activate motor cortex and that current does not substantially spread outside the stimulation area. Computational models predict that both TES and tDCS waveforms using the 4×1-Ring configuration generate electric fields in cortex with comparable gross current distribution, and preferentially directed normal (inward) currents. The agreement of modeling and experimental data for both current delivery and focality support the use of the HD-tDCS 4×1-Ring montage for cortically targeted neuromodulation. ► Experimental transcranial electrical stimulation validates MRI-derived model of brain current delivery. ► High-Definition tDCS focally delivers current to motor cortex. ► Both TES and tDCS produce inward (normal) currents beneath the anode. ► The High-Definition electrode montage could be used for focal therapeutic tDCS.